The Effects of Different Concentrations of Hydrogen-Rich Water on the Growth Performance, Digestive Ability, Antioxidant Capacity, Glucose Metabolism Pathway, mTOR Signaling Pathway, and Gut Microbiota of Largemouth Bass (Micropterus salmoides) - Yin Yuan; Huixiang Li; Songwei Chen; Yongchun Lin; Jiangyuan Peng; Junru Hu; Yongsheng Wang (Fishes, 2024)
Hydrogen-rich water (HRW) is widely recognized for its growth promoting, antioxidant, and anti-inflammatory properties. However, little is known about the role of HRW in aquaculture. This study aims to investigate how different concentrations of HRW affect the growth performance, digestive ability, antioxidant capacity, mTOR signaling pathway, and gut microbiota of juvenile largemouth bass. We randomly assigned 360 fish (13.73 ± 0.1 g) to three treatments. The control group was maintained in regular water, while the treatment groups were treated with different concentrations of H2 dissolved in water, which were H1 (179.65 ± 31.95 ppb) and H2 (280.65 ± 64.43 ppb), respectively. Through an analysis of the three treatments, it was found that H1 significantly increased the final body weight, weight gain rate, specific growth rate, and survival rate, and reduced the feed conversion ratio (p